ANALYSIS OF THE SPEED OF CHILDREN OF THE 46TH KINDERGARTEN ON MARGILANSKAYA STREET - Axunov Javlon Abdujalilovich (Journals Park Publishing, 2022)
This article discusses the speed of children in order to ensure the safety of pedestrians on the streets where educational institutions are located.
Keywords: speed; pedestrian; density